2014
DOI: 10.1152/japplphysiol.01322.2013
|View full text |Cite
|
Sign up to set email alerts
|

The aging mouse partially models the aging human spine: lumbar and coccygeal disc height, composition, mechanical properties, and Wnt signaling in young and old mice

Abstract: Murine lumbar and coccygeal (tail) regions of spines are commonly used to study cellular signaling of age-related disc diseases, but the tissue-level changes of aging intervertebral discs and vertebrae of each spinal region remain unclear. Furthermore, the impact of aging lumbar and coccygeal discs on Wnt/β-catenin signaling, which is putatively involved in the catabolism of intervertebral discs, is also unclear. We compared disc/vertebrae morphology and mechanics and biochemical composition of intervertebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 59 publications
6
40
0
Order By: Relevance
“…Alongside the loss of Wnt signaling with aging and compression, cell membrane receptor for Wnt ligands LRP5 was reduced with aging and compression. Next, we showed that 1 month‐deletion of LRP5 in OSX‐expressing of young‐adult mice impaired Wnt signaling and induced IVD degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside the loss of Wnt signaling with aging and compression, cell membrane receptor for Wnt ligands LRP5 was reduced with aging and compression. Next, we showed that 1 month‐deletion of LRP5 in OSX‐expressing of young‐adult mice impaired Wnt signaling and induced IVD degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, the NP, AF, and boundary between the NP and AF of the IVD were scored and added together for a total IVD score. Wnt activity (LacZ expression) quantification within the NP and AF were carried out as previously described . For instrumented animals, tail IVDs between CC7‐9 and CC10‐12 and, for genetic mouse models, tail IVDs CC10‐12 and lumbar discs L3‐5 were separated from all other tissues and snap frozen in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…The power of this approach lies in its consistency, versatility, and capability for high-resolution imaging. Our approach here demonstrates that it is possible to culture both lumbar and caudal IVDs, but it is important to note that these discs are anatomically different across aging and development 15 . As such, our experimental design randomizes the lumbar and caudal levels separately.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller sized animals such as the mouse and rat (recently Bailey et al, ; Holguin et al, ; Jin et al, ; Miyagi et al, ; Pelle et al, ) as well as larger animals such as the pig (recently Ivicsics et al, ; Hebelka et al, ; Yilgor et al, ), sheep (recently Reitmaier et al, ; Wade et al, ), and cow tail (recently Chan and Gantenbein‐Ritter, ; Eder et al, ; Farrell and Riches, ) have been extensively used in the literature. Substantial work has also been conducted on verifying the suitability of such animal models for the study of IVD disorders (Wilke et al, ; Beckstein et al, ; Neidlinger‐Wilke et al, ; Ohtori et al, ; comprehensive reviews by Alini et al, and Singh et al, ).…”
Section: Introductionmentioning
confidence: 99%